2017
DOI: 10.4209/aaqr.2017.01.0048
|View full text |Cite
|
Sign up to set email alerts
|

How the Atmosphere over Eastern Himalaya, India is Polluted with Carbonyl Compounds? Temporal Variability and Identification of Sources

Abstract: A study was conducted on atmospheric carbonyl compounds for the first time over a Himalayan atmosphere in India. Samples were collected from a high altitude hill station, Darjeeling (27.01°N, 88.15°E, 2200 masl) during June 2012 to May 2013. Temporal variation, meteorological influence, source apportionment and ozone formation potential etc were studied for acetaldehyde, formaldehyde, acetone, butanaldehyde, propanaldehyde, benzaldehyde, crotonaldehyde, valeraldehyde, isovaleraldehyde, hexanaldehyde, p-toluald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 103 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…In another study Khare et al, (1997b) reported an average 0.8 ± 0.5 ppb (ranging 0.2 -2.8 ppb) HCHO in a semiarid region in northern India, with a peak in the afternoon at ~3-7 pm during February, 1995. Recently Sarkar et al (2017) reported annually averaged HCHO concentrations of 11.6 ± 16.3 µg m -3 (9.5 ± 13.3 ppb)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In another study Khare et al, (1997b) reported an average 0.8 ± 0.5 ppb (ranging 0.2 -2.8 ppb) HCHO in a semiarid region in northern India, with a peak in the afternoon at ~3-7 pm during February, 1995. Recently Sarkar et al (2017) reported annually averaged HCHO concentrations of 11.6 ± 16.3 µg m -3 (9.5 ± 13.3 ppb)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ethanol has low reactivity for ozone formation, however aldehydes are produced in its burning which have high reactivity for O 3 formation, impacting the chemistry of the atmosphere, contributing to the formation of radicals and photochemical processing in the atmosphere (Goldan et al, 2004;de Gouw et al, 2012). Ethanol in the atmosphere is converted into acetaldehyde, a highly reactive compound for ozone formation, which is also toxic to human health (Sarkar et al, 2017). Ethanol was the highest concentration VOCs found in the 2011/2012 campaign, followed by acetaldehyde in this study.…”
Section: Concentrations Of Volatile Organicmentioning
confidence: 99%
“…These two species have been targeted in numerous toxicological studies owing to their deleterious health effects (Health and Services, 1999; Neghab et al, 2017; Salthammer et al, 2010; Til et al, 1988; Tunsaringkarn et al, 2012b, 2012c). Their ubiquity and importance in ambient air have been documented in many past studies (Lü et al, 2016; Neghab et al, 2017; Sarkar et al, 2017). Owing to rapid global urbanization and population growth, characterizing the concentrations and health effects of these aldehyde species is important as vehicular emissions are a major pollutant source in urban centers (Bauri et al, 2016; Crosbie et al, 2014; Hazrati et al, 2016b; Mannucci and Franchini, 2017; Masih et al, 2016; Morknoy et al, 2011; Rad et al, 2014; Sarkar et al, 2017; Saxena and Ghosh, 2012; Tunsaringkarn et al, 2014).…”
Section: Introductionmentioning
confidence: 95%